2012
DOI: 10.1038/aps.2012.47
|View full text |Cite
|
Sign up to set email alerts
|

The dual role of osteopontin in acetaminophen hepatotoxicity

Abstract: Aim: Osteopontin (OPN), a multifunctional protein, has been reported to be protoxicant in acetaminophen hepatotoxicity. In this study, the mechanisms underlying the detrimental role of OPN in acetaminophen toxicity were explored. Methods: Male C57BL/6 (wild-type, WT) and OPN -/-mice were administered with acetaminophen (500 mg/kg, ip). After the treatment, serum transaminase (ALT), as well as OPN expression, histology changes, oxidative stress and infl ammation response in liver tissue were studied. Freshly is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Moreover, OPN levels are associated with the degree of liver necrosis in acute liver injury; however, its involvement in preventing the progression of liver disease requires further investigation (Arai et al, 2006;Srungaram et al, 2015). In mice, OPN deficiency served to restrict neutrophil infiltration and macrophage accumulation and inhibited the release of pro-inflammatory cytokines (He et al, 2012). Similarly, by blocking OPN expression, the sensitivity to acetaminophen was reduced and mice developed the capacity to survive a drug overdose (Arai et al, 2006;He et al, 2012).…”
Section: Osteopontin (Opn)mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, OPN levels are associated with the degree of liver necrosis in acute liver injury; however, its involvement in preventing the progression of liver disease requires further investigation (Arai et al, 2006;Srungaram et al, 2015). In mice, OPN deficiency served to restrict neutrophil infiltration and macrophage accumulation and inhibited the release of pro-inflammatory cytokines (He et al, 2012). Similarly, by blocking OPN expression, the sensitivity to acetaminophen was reduced and mice developed the capacity to survive a drug overdose (Arai et al, 2006;He et al, 2012).…”
Section: Osteopontin (Opn)mentioning
confidence: 99%
“…In mice, OPN deficiency served to restrict neutrophil infiltration and macrophage accumulation and inhibited the release of pro-inflammatory cytokines (He et al, 2012). Similarly, by blocking OPN expression, the sensitivity to acetaminophen was reduced and mice developed the capacity to survive a drug overdose (Arai et al, 2006;He et al, 2012). However, another study evidenced that OPN improved the survival of hepatocytes in diethylnitrosamine-induced liver injury via inhibition of NF-kB activation and reduced production of inflammatory mediators .…”
Section: Osteopontin (Opn)mentioning
confidence: 99%
See 1 more Smart Citation
“…Because APAP-induced hepatic injury occurs in several steps, KA and Ac 2 KA may exert protective effects against multiple steps of APAP action. Initially, we hypothesized that KA and Ac 2 KA were antioxidants, as the antioxidant natural products, which are known to prevent APAP-induced hepatic injury (6,8). Several investigations have reported that ent-kaurene diterpenoid compounds exert antioxidant activities (4,19).…”
Section: Discussionmentioning
confidence: 99%
“…213,214 Osteopontin has also proinflammatory effects by promoting the migration of macrophages and neutrophils. 200,215 In HCC osteopontin acts via different biological processes, contributing HCC metastasis, 216,217 proliferation, 218 EMT, 219,220 and resistance to apoptosis. 210,216…”
Section: Growth Factors and Cytokinesmentioning
confidence: 99%